2009
DOI: 10.1021/la901822h
|View full text |Cite
|
Sign up to set email alerts
|

Capping and Passivation of Aluminum Nanoparticles Using Alkyl-Substituted Epoxides

Abstract: We report here on the synthesis and passivation of small (20-30 nm) aluminum nanoparticles using alkyl-substituted epoxides as capping agents. FTIR and 13C NMR spectroscopy indicate that the epoxides polymerize to form a polyether cap on the surfaces of the aluminum nanoparticles. Nanoparticles capped with epoxyhexane and epoxydodecane are stable in air, but particles capped with epoxyisobutane are pyrophoric. TEM images show spherical Al particles. Powder X-ray diffraction shows the presence of crystalline Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 14 publications
0
50
1
Order By: Relevance
“…This is consistent with the idea that AlCp or AlCp* removal is the initial decomposition step and that steric hindrance from the ligand is an important limiting mechanism for monomer detachment. We also note that the tetramer Al 4 (C 5 Me 4 H) 4 , in which each Cp ligand has four methyl groups instead of five as in Cp*, has also been experimentally observed in solid state form, further suggesting the necessity of strong steric hindrance for cluster stability. 14 Combustion Properties.…”
Section: ' Computational Methodologymentioning
confidence: 59%
See 4 more Smart Citations
“…This is consistent with the idea that AlCp or AlCp* removal is the initial decomposition step and that steric hindrance from the ligand is an important limiting mechanism for monomer detachment. We also note that the tetramer Al 4 (C 5 Me 4 H) 4 , in which each Cp ligand has four methyl groups instead of five as in Cp*, has also been experimentally observed in solid state form, further suggesting the necessity of strong steric hindrance for cluster stability. 14 Combustion Properties.…”
Section: ' Computational Methodologymentioning
confidence: 59%
“…This implies that the MÀL bond is much stronger than the AlÀAl bonds, as would be expected. The same is true for Al 4 Cp 4 *, where the MÀL BDE of 44.89 kcal/mol is much higher than the tetramerization energy of 9.09 kcal/mol. Previous calculations by Huber and Schn€ ockel using BP86 and an SVP basis set also showed that Al 4 Cp 4 is more stable against decomposition into monomers than Al 4 Cp 4 *.…”
Section: ' Computational Methodologymentioning
confidence: 67%
See 3 more Smart Citations